Picnic : pop-folk contemporary illustration - Retina; Retinette (Barcelona : Promopress, 2011)
'Picnic' is the compilation of the best works from the new-wave of international young artists setting new directions in modernist and folkloric illustration.
Includes index.
Text in English, French and Spanish.
boek